Central giant-cell granuloma located in the mandibular symphyseal region of a child - Bonolis Aurélien; Euvrard Edouard; Meyer Christophe; Louvrier Aurélien (EDP Sciences, 2018)
Introduction: Central giant-cell granuloma (CGCG) is a rare mandibular tumor. The originality of this case lies in its clinical presentation, with a delay in treatment despite a significant aesthetic impact. Observation: An 8-year-old boy whose chin had been swelling for three (3) months was referred to have a consultation. The medical imaging examination revealed a well-defined osteolytic lesion of about 3 cm and round in shape. The lesion was surgically treated by enucleation. The anatomopathological examination provided evidence of a CGCG. Conclusion: Postoperative period was aesthetically acceptable, there were no nervous or dental lesions and no relapse at the 6-month follow-up.